RAILS AND POINTED CONDUCTORS - Abdurakhmanov Shavqiddin Mukhtarovich; Rasulov Khurshid Kuvandikovich (Bright Mind Publishing, 2026)
This scientific article analyzes the structural characteristics, operational loading behavior, and modernization challenges of rails and railway turnouts as key components of railway track superstructure using a DSc-level systematic approach. The study investigates rail metal fatigue, contact stresses, dynamic load effects, geometric accuracy of rail profiles, and impact forces occurring in turnout transition zones. Particular attention is given to increasing axle loads, higher train speeds, and the transition to modern high-speed railway systems, which impose new technical requirements on rails and turnouts. The effectiveness of structural improvements, material strengthening, elastic foundations, and dynamic load reduction methods is evaluated through analytical calculations. The results provide scientific and practical recommendations aimed at enhancing reliability and safety of railway infrastructure.
Keywords: Rails, railway turnouts, track superstructure, dynamic load, contact stress, fatigue process, reconstruction, modernization.